Astatination of nanoparticles containing silver as possible carriers of 211At - Kucka, Jan; Hrubý, Martin; Konák, Cestmír; Kozempel, Ján; Lebeda, Ondrej (Applied radiation and isotopes, 2006)
The alpha emitter 211At is a prospective radionuclide for the therapy of smaller tumours and metastases. However, the chemical properties of 211At together with the fact that it is available only in trace amounts, makes the labelling of prospective astatine carriers rather complicated. In this context we have studied a new class of possible astatine carriers--nanoparticle systems, which tend to concentrate themselves in some types of tumours by means of the EPR effect. Additionally, such nanoparticles have the advantage that they may be chemically modified by the attachment of a tumour-seeking agent, and also directly applied to the target site. In order to reach high labelling yields, and in order to protect the nanoparticles from rapid degradation by the immune system, silver-containing particles covalently coated by poly(ethylene oxide) were developed and tested. The effect of the different reducing and oxidizing agents on the labelling yield was also determined. It was found that labelling yields were almost quantitative and well reproducible under reducing conditions, while under oxidizing conditions they dropped to ca. 50%. In the absence of any reducing or oxidizing agent, the labelling yields were randomly distributed between a range of 50% and 97%. The labelled nanoparticles were stable even in a large surplus of competing chloride ions.